E-Learning as a Boosting Factor of Soft Skills in the Teaching of Administration Science: The Case of Universidad Estatal a Distancia (UNED), Costa Rica - Mora Vicarioli, Francisco (2020)
Soft skills are competencies that have taken a leading role in the business and working world for a proper performance in different disciplinary areas. The professionals in administration sciences do not escape this important need; in this research, the use of the virtual modality (e-learning) and its support in the teaching of the aforementioned sciences is described to foster the development of soft skills in students from the Distance State University of Costa Rica (UNED). The collaboration of 32 professionals in the field of administration with both professional and university teaching experience was obtained, which provided findings, such as recognition of the relevance of e-learning for the development of technological skills and soft skills; in the latter, time management and communication in different ways stood out. There was also the participation of 51 students of administration sciences who contributed points of view and allowed a contrast with the teaching perspective. Some challenges that are proposed are the need for training in this regard and the short time in the academic period available to include activities that strengthen these skills or abilities.